PARSA Coconut Farm - Yaris, Petrus; Amiruddin, Andi Nur Atika; Ali, Ruzilah; Kamarudzain, Shahzunah; Matshah, Nuralyani Nazirah (2013)
The name of our business is PARSA Coconut Farm. The variety of coconut we plant is Matag Coconut. MATAG is a short form or a nick name of new hybrid coconut which is from original coconut from Malaysia which is Malaysia Yellow Dwarf (MYD) or Malaysia Red Dwarf (MRD) with Tagnanan coconut from Philippine. The coconut produced by MATAG coconut tree is suitable for variety of uses such as for coconut water, coconut milk production, and also for grated coconut. In Sabah , the production of coconut is always low than the demand. Hence , we are planning to be the largest supplier to provide enough coconut demand in Sabah especially. Our business is located in Kg Tanjung Bangau , Kudat Sabah. The location is choose by the suitability if the coconut tree to growth. Hence , we found that Kudat are the most suitable place for our business. Although the location of our farm in Kudat area , but our target market is in the Tuaran area. This is because , we notice that the demand of coconut in that area is high while the supplier is low. So , we take the opportunity to make a profit by become a supplier in that area.